2022
DOI: 10.1371/journal.pbio.3001555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cationic glycolipid in Streptococcus agalactiae that contributes to brain entry and meningitis

Abstract: Bacterial membrane lipids are critical for membrane bilayer formation, cell division, protein localization, stress responses, and pathogenesis. Despite their critical roles, membrane lipids have not been fully elucidated for many pathogens. Here, we report the discovery of a novel cationic glycolipid, lysyl-glucosyl-diacylglycerol (Lys-Glc-DAG), which is synthesized in high abundance by the bacterium Streptococcus agalactiae (Group B Streptococcus, GBS). To our knowledge, Lys-Glc-DAG is more positively charged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…The LTA profiles observed in B. subtilis and S. aureus lacking MprF (seen as shorter and/or decreased in abundance) and the overexpression of B. subtilis MprF (causing a smeared & retarded mobility of the LTA) ( Fig 4B, 6A ) suggest that MprF positively regulates LTA production ( Fig 8A ). Other studies have indicated that MprFs may have relaxed substrate specificities across species (22, 62) and even synthetise lysyl-glucosyl-DAG glycolipid in Streptococcus agalactiae (63). Recently, it has been shown that when S. aureus LtaS uses PGol as an alternative anchor to the glycolipid produced by UgtP, the concentration of these free lipid starter units regulates the length of the LTA polymerised in vitro (33).…”
Section: Discussionmentioning
confidence: 99%
“…The LTA profiles observed in B. subtilis and S. aureus lacking MprF (seen as shorter and/or decreased in abundance) and the overexpression of B. subtilis MprF (causing a smeared & retarded mobility of the LTA) ( Fig 4B, 6A ) suggest that MprF positively regulates LTA production ( Fig 8A ). Other studies have indicated that MprFs may have relaxed substrate specificities across species (22, 62) and even synthetise lysyl-glucosyl-DAG glycolipid in Streptococcus agalactiae (63). Recently, it has been shown that when S. aureus LtaS uses PGol as an alternative anchor to the glycolipid produced by UgtP, the concentration of these free lipid starter units regulates the length of the LTA polymerised in vitro (33).…”
Section: Discussionmentioning
confidence: 99%
“…Aminoacylation is not specific to PG and in the case of Listeria , Lys-CL is observed [ 10 ]. Furthermore, the amino-acylated glycolipid, lysyl-glucosyl-diacylglycerol (Lys-Glc-DAG) was recently identified in Streptococcus agalactiae ( Table 1 ) [ 11 ]. In general, amino-acylation aids in masking the negative charge associated with the extracellular surface of the membrane that is attributed to the phosphate headgroup of phospholipids, which has beneficial implications for human pathogens.…”
Section: Amino-acylation Modifications: One Size Doesn’t Fit Allmentioning
confidence: 99%
“…S . aureus Δ mprF strains are significantly attenuated in blood survival in vivo, whereas Enterococcal and Streptococcal strains were not [ 8 , 11 , 13 ]. Removal of Lys-PG from the membrane of Staphylococci and Enterococci resulted in a significant reduction of the negative extracellular surface charge creating a more neutral surface charge, which decreased susceptibility to CAMPs, antibiotics, and opsonophagocytic killing by neutrophils [ 8 , 13 , 14 ].…”
Section: Amino-acylation Modifications: One Size Doesn’t Fit Allmentioning
confidence: 99%
See 2 more Smart Citations